Parallel processing in human visual cortex revealed through the influence of their neural responses on the visual evoked potential. - Marcar, V.L.; Battegay, E.; Schmidt, D.; Cheetham, M. (Vision Research, 2022)
The neural response in the human visual system is composed of magno-, parvo- and koniocellular input from the retina. Signal differences from functional imaging between health and individuals with a cognitive weakness are attributed to a dysfunction of a specific retinal input. Yet, anatomical interconnections within the human visual system obscure individual contribution to the neural response in V1. Deflections in the visual evoked potential (VEP) arise from an interaction between electric dipoles, their strength determined by the size of the neural population active during temporal - and spatial luminance contrast processing. To investigate interaction between these neural responses, we recorded the VEP over visual cortex of 14 healthy adults viewing four series of windmill patterns. Within a series, the relative area white in a pattern varied systematically. Between series, the number of sectors across which this area was distributed doubled. These patterns were viewed as pattern alternating and on-/off stimuli. P100/P1 amplitude increased linearly with the relative area white in the pattern, while N135/N1 and P240/P2 amplitude increased with the number of sectors of which the area white was distributed. The decreases P100 amplitude with increasing number of sectors is attributed to an interaction between electric dipoles located in granular and supragranular layers of V1. Differences between the VEP components obtained during a pattern reversing display and following pattern onset are accounted for by the transient and sustained nature of neural responses processing temporal - and spatial luminance contrast and ability of these responses to manifest in the VEP.